Cytomegalovirus Antibodies Amongst Immunocompromised (HIV) Patients At Lagos University Teaching Hospital (LUTH) Idi - Araba, Lagos - Akinbami, AA; Akanmu, AS; Adeyemo, TA; Wright, KO; Dada, MO; Dosunmu, AO (Journal of Medicine, 2010)
Background: CMV infection constitutes a real risk of pathogenecity in immunocompromised patient. HIV- infected patients who require transfusion are at high risk of developing symptomatic CMV infection when they are transfused with CMV-infected donor blood. This study intends to determine CMV infection risk in correlation with blood transfusion in a population of HIV- infected patients Methods: The study was carried out amongst clients attending HIV clinic at Lagos University Teaching Hospital (LUTH), who were recruited consecutively. Replacement blood donors of the hospital were recruited as controls. A total of 10mls of blood sample was collected per consenting participant. The serum obtained from 5ml of blood was assayed for CMV IgG/IgM using an enzyme- linked immunosorbent assay (ELISA) based Kit whilst full blood count and CD4 cell counts were also performed on the remaining 5mls. Results: A total of 129 HIV-infected were studied. All (100%) were IgG anti-CMV positive. 8 (6.6%) were IgM anti- CMV positive. This difference was found to be statistically significant P=0.004, (P<0.05). Of 122 replacement blood donor controls, 118 (96%) of them were IgG anti-CMV positive whilst 26 (19.5%) of 121 were IgM anti-CMV positive.The mean CD4+ cell count of HIV-infected patients was (234 ± 173.181). Previous history of blood transfusion did not affect CMV antibody positivity directly. Conclusion: The seroprevalence of CMV is very high in HIV-infected patients, which is comparable to the seroprevalence amongst the general population The use of leukoreduced blood units for anaemic HIV infected patients, is recommended. Keywords: Seroprevalence; CMV IgG/IgM; ELISA; healthy blood donors; HIV-infected patients. DOI: 10.3329/jom.v11i2.5462 J MEDICINE 2010; 11 : 151-154